The Effectiveness of Crossword Puzzle in Improving Mufradat Skills - Khaira, Mutia (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2021)
Arabic mufradat is an element of various language elements, where the richness of vocabulary is part of the indicator of language proficiency. In reality, vocabulary learning often encounters obstacles, therefore choosing the right media is part of an effort to overcome the existing difficulties. This study aimed to test the effectiveness of the puzzle in improving Arabic vocabulary skills. This study was conducted with a quasi-experimental approach where data were obtained through pre-test and post-test. Based on the results, the use of puzzle games as learning media was effective to improve mufradat skills.